Performance of Public Procurement Goods and Services Units in Ogan Ilir Regency - Adesta Midkasna; Kgs. M. Sobri; Abdul Nadjib (Universitas Medan Area, 2022)
This paper examines the performance of Public Procurement Goods/Services Units in Ogan Ilir Regency based on balanced scorecard. Balanced scorecard has four perspectives, namely customer, internal business process, learning and growth and financial perspectives. The research method used is descriptive quantitative. Data were obtained through a rating scale questionnaire from 140 respondents consisting of 21 internal and 119 customers using the PLS-SEM. The results showed that the performance of UKPBJ Ogan Ilir is high with the customer, internal business processes and learning and growth perspective have a significant effect on the performance of UKPBJ Ogan Ilir whereas the financial perspective does not significantly influence the performance of UKPBJ Ogan Ilir. Based on research findings that there are weaknesses in the advice dimension (customer) and innovation dimension (internal business process) and advantages in the learning and growth and financial perspective, its suggest to maintains employee discipline, responsiveness and developing innovations to continuously improved public procurement service, maintaining financial accountability, prioritizing employees who have the ability in the field and accelerating the transformation of functional profession of public procurement goods/services.